The life and times of the Thunderbolt Kid - Bryson, Bill (Black Swan, 2007)
Some say that the first hint that Bill Bryson was not of Planet Earth came when his mother sent him to school in lime-green Capri pants. Others think it all started with his discovery, at the age of six, of a woollen jersey of rare fineness. In this memoir, he explores the ordinary kid he once was, and the curious world of 1950s America.